The relationship between service quality, customer satisfaction and customer loyalty towards KTMB (Commuter) / Norshafina Abdullah - Abdullah, Norshafina (Faculty of Business and Management, 2007)
This research is about a study on relationship between factors influencing customer loyalty on KTMB (Commuter). Five dimension of service quality in terms of tangible, reliability, responsiveness, assurance, empathy and also customer satisfaction in terms of customer expectation and perception have been identified in order to investigate whether or not these factors have a relationship with customer loyalty . This research is conducted in order to identify whether the service quality that KTMB (Commuter) delivered to their customer meets their satisfaction and make them loyalty to this firm. The objective of this research are to determine whether service quality (tangible, reliability, responsiveness, assurance and empathy) has a direct impact on customer loyalty, to examine whether customer satisfaction (expectation and perception) has a direct impact on customer loyalty, to determine whether service quality has a direct impact on customer satisfaction and to identify a good solution on how to delivered best service to customer. The survey is conducted at KTM Commuter Stations. Sampling technique that has been used in this research is convenience sampling. The sample size for this study is 90 customers who are also have experience in using KTMB (Commuter). Respondents are required to answer the questionnaires and the data will be analyzed SPSS version 15.0 will be used to summarize the data. The result of reliability testing is 0.849 and all the data has answered my research objective by using One-Way ANOVA to test the hypothesis and also cross tabulation and correlations.